A cross-sectional survey of mental health clinicians’ knowledge, attitudes, and practice relating to tobacco dependence among young people with mental disorders - Kulkarni, Meghana; Huddlestone, Lisa; Taylor, Anne; Sayal,, Kapil; Ratschen, Elena (BioMed Central, 2014)
BACKGROUND: Mental health services in England are smoke-free by law and expected to provide comprehensive support to patients who smoke. Although clinicians’ knowledge in this area is reported to be limited, research exploring the issue in Child and Adolescent Mental Health Services (CAMHS) is lacking. This study aimed to investigate the knowledge, attitudes, and practice of clinicians working within specialist and highly specialist Child and Adolescent Mental Health Services (CAMHS) relating to tobacco dependence, its treatment and its relation to mental disorder.